The Portuguese Man-of-War Has Always Entered the Mediterranean Sea—Strandings, Sightings, and Museum Collections - Tiralongo, Francesco; Badalamenti, Rosario; Arizza, Vincenzo; Prieto, Laura; Lo Brutto, Sabrina (Frontiers in Marine Science, 2022)
A search of records from different kinds of sources namely, scientific and grey literature, social media, and zoological museum collections, has been carried out to review the incidence of Physalia physalis (Linnaeus, 1758), the Portuguese man-of-war, in the Mediterranean Sea. The temporal frame of the records, considered valid if documented with images or collected specimens, ranged from the second half of the 18th century to the year 2021. Thanks to colonies preserved in some Italian historical museum collections, originating from the western basin, it was possible to date the putative first documented record of P. physalis of the Mediterranean Sea in 1850. The dataset shows some massive strandings that occurred in localities of the Strait of Gibraltar and Alboran Sea, the area of the entrance, from the Atlantic towards the Mediterranean waters, and the starting point from where the species spread towards the western and central basin. Physalia physalis does not reach the eastern area of the Mediterranean Sea. As the records of this species from the Italian maritime regions were abundant in the summertime and considering the danger related to contact with humans, they were subdivided into three categories of risk according to the months of occurrence. These categories were created to assign a level of danger for swimmers. The increasing sightings of such a poisonous cnidarian in coastal waters can represent a risk to human health, and a threat to all those activities linked to the marine tourism sector. The overview given goes beyond scientific purposes and aims to reach society and public administrators. The involvement of citizens and touristic structures for the early detection of P. physalis can play a key role in preventing encounters with the species, allowing marine tourist facilities to operate within a range of reasonable security.